Periodic patterning stem cells and induction of skin appendages: p-ERK-dependent mesenchymal condensation is coupled with Turing mechanism to convert stripes to spots - Lin, C; Jiang, T; Baker, R; Maini, P; Hughes, M; Widelitz, R; Chuong, C (2008)
n/a